TEACHERS’ PERSPECTIVES ON EDUCATIONAL INCLUSION: ANALYZING THE ROLE OF GENDER, EXPERIENCE, AND INTERACTION - Soni, Chandrika; Singh, Preeti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study highlights the critical role of education in promoting the social inclusion of children with disabilities, focusing on global and Indian policy frameworks such as NEP 2020. It examined university teachers' attitudes towards inclusive education intending to bridge the gap in policy implementation due to challenges faced by educators and contribute to creating a more inclusive academic environment. This exploratory-cum-descriptive study adopted a survey-based quantitative research design to explore the attitudes of 115 randomly selected teachers from the 10 purposively selected higher education institutions in Rajasthan. This study adopted the Teacher Inclusion Attitude Scale developed by Ernst and Rogers (2009) to collect data using the 5-point Likert response method and used SPSS software to conduct an analysis of variance and t-test on the data. The study revealed that gender and teaching experience do not significantly influence university teachers' attitudes toward educational inclusion, but prior interaction with people with disabilities significantly shapes their perspectives on educational inclusion. Thus, the study emphasizes policymakers to prioritize teacher training programs that directly engage with people with disabilities to encourage inclusive attitudes in higher education.